TINGKAT PENGETAHUAN BIDAN TENTANG MANAJEMEN AKTIF KALA III DI RSUD. DR. TENGKU MANSYUR KOTA TANJUNG BALAI FEBRUARI 2019 - MENI TANJUNG (LP2MTBM MAKARIOZ, 2019)
Kala III of labor is Kala uri is the birth of a baby and ends with the birth of the placenta and membranes. Active management of Kala III is management of placental expenditure, most cases of morbidity and maternal death in Indonesia are caused by uterine atony and placental retention that can actually be prevented by active management of Kala III. In the world it is estimated that 15,000 of the approximately 4.5 million women giving birth in Indonesia experience complications that cause death. This research is descriptive in nature, aiming to find out the level of knowledge of midwives about the management of active management of Kala III in the General Hospital. Tengku Mansyur. Where all populations sampled in this study amounted to 30 midwives by giving questionnaires directly. The results of the study on respondents found that the level of knowledge of midwives about management of kala iii based on the age of the majority knowledgeable enough in the age group> 35 years as many as 7 people (23.3%). Based on the education of the knowledgeable majority in the D-III Midwifery group of 13 people (43.3%). Based on the Length of Work, the majority of people who are Good and Enough are as many as 10 people (33.3%). From this research it is expected that midwives always attend training courses held to improve and update skills on Active Management kala III